KOORDINASI KEPALA DUSUN DALAM PENYELENGGARAAN TUGAS KEWILAYAHAN DI DESA CISADAP KECAMATAN CIAMIS KABUPATEN CIAMIS - Yordan Renaldo Putra; Agus Nurulsyam Suparman; Regi Refian Garis (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study is motivated by the suboptimal coordination of Hamlet Heads (Kepala Dusun) in carrying out territorial duties in Cisadap Village, Ciamis District. The Hamlet Heads are still less effective in supervision, community development, and managing social service programs. The research problem is how the Hamlet Heads coordinate in implementing territorial duties in Cisadap Village. The study applies Hasibuan’s (2019) theory, which identifies four dimensions of coordination: sense of cooperation, rivalry, team spirit, and esprit de corps. The research uses a descriptive qualitative method with eight informants, consisting of the Village Head, Hamlet Heads, and community representatives. The results show that the coordination of Hamlet Heads is not yet fully optimal. The sense of cooperation dimension functions well through regular communication and harmonious collaboration, while the other three dimensions remain weak due to decision-making dominance, uneven participation, and a lack of inter-hamlet solidarity. The main obstacles include inconsistent communication, differing viewpoints, low community participation, and misaligned task distribution. Improvement efforts are carried out through enhanced communication, regular coordination meetings, participatory deliberations, involvement of neighborhood (RT/RW) and community members, and cross-hamlet collaborative activities to strengthen solidarity and unity.